A new species of Nuuanu (Crustacea, Amphipoda, Nuuanuidae) from a Caribbean coral reef with identification keys to males and females of Nuuanu species - Ortiz, Manuel; Winfield, Ignacio (Zootaxa, 2017)
A new species of amphipod of the genus Nuuanu is described and illustrated, and is diagnosed against the morphologically most similar species. It was collected in coral rubble from a tropical coral reef, NW Caribbean Sea. The new species increases the number of Nuuanu species recorded to 20 worldwide. Nuuanu jaumei sp. nov., can be distinguished from other members of the genus by a combination of characters: head with bigeminal dispersed eyes; mammiliform lateral cephalic lobe; anteroventral notch of head well defined; antenna 1 geniculate; accessory flagellum 3–articulate; coxa 5 devoid of seta on ventromedial margin; article 2 anteroventral corner of pereopod 5 with a strong setae; epimera 1, 2, 3 with 2, 4, 1 ventral robust setae respectively; telson longer than broad; female gnathopod 2 with 2 long and slender setae on posterior margin. In addition, a key for the identification of all known male species of the genus Nuuanu, and another for the identification of the females, are also presented.